Accounting Conservatism and Liquidity Management - hasan zalaghi; morteza bayat (پژوهش‌های تجربی حسابداری, 2015)
This study examines the relation between accounting conservatism and liquidity management. The sample consists of 76 firms listed in TSE in the period from 2005 to 2012. To test the hypothesis, regression coefficient analysis has been used. First, accounting conservatism has been measured by Gyvly and Hime model and then to measure the effects of accounting conservatism on cash and tendency to saving is measured by Kahal Batz et.al (2009) and Almeida et.al (2004) models respectively. Empirical evidence suggests that there is a significant relationship between conservatism and management of liquidity. Also between accounting conservatism and thetendency to saving there is a significant negative relation. The research results show of the more conservatism, the less cash available for firms.